A paradigmatic change: Linking fullerenes to electron acceptors - Feng, Lai; Rudolf, Marc; Wolfrum, Silke; Troeger, Anna; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Ameri, Tayebeh; Brabec, Christoph; Guldi, Dirk Michael (Journal of the American Chemical Society, 2012)
The potential of Lu N@C and its analogues as electron acceptors in the areas of photovoltaics and artificial photosynthesis is tremendous. To this date, their electron-donating properties have never been explored, despite the facile oxidations that they reveal when compared to those of C . Herein, we report on the synthesis and physicochemical studies of a covalently linked Lu N@C -perylenebisimide (PDI) conjugate, in which PDI acts as the light harvester and the electron acceptor. Most important is the unambiguous evidence-in terms of spectroscopy and kinetics-that corroborates a photoinduced electron transfer evolving from the ground state of Lu N@C to the singlet excited state of PDI. In stark contrast, the photoreactivity of a C -PDI conjugate is exclusively governed by a cascade of energy-transfer processes. Also, the electron-donating property of the Lu N@C moiety was confirmed through constructing and testing a bilayer heterojunction solar cell device with a PDI and Lu N@C derivative as electron acceptor and electron donor, respectively. In particular, a positive photovoltage of 0.46 V and a negative short circuit current density of 0.38 mA are observed with PDI/Ca as anode and ITO/Lu N@C as cathode. Although the devices were not optimized, the sign of the V and the flow direction of J clearly underline the unique oxidative role of Lu N@C within electron donor-acceptor conjugates toward the construction of novel optoelectronic devices. © 2012 American Chemical Society.

Coordinative interactions between porphyrins and C60, La@C 82, and La2@C80 - Tsuchiya, Takahiro; Rudolf, Marc; Wolfrum, Silke; Radhakrishnan, Shankara Gayathri; Aoyama, Ryo; Yokosawa, Yuya; Oshima, Azusa; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Chemistry - A European Journal, 2013)
For the first time, a C derivative (1) and two different lanthanum metallofullerene derivatives, La@CPy (2) and La @CPy (3), that feature a pyridyl group as a coordination site for transition-metal ions have been synthesized and integrated as electron acceptors into coordinative electron-donor/electron-acceptor hybrids. Zinc tetraphenylporphyrin (ZnP) served as an excited-state electron donor in this respect. Our investigations, by means of steady-state and time-resolved photophysical techniques found that electron transfer governs the excited-state deactivation in all of these systems, namely 1/ZnP, 2/ZnP, and 3/ZnP, whereas, in the ground state, notable electronic interactions are lacking. Variation of the electron-accepting fullerene or metallofullerene moieties provides the incentive for fine-tuning the binding constants, the charge-separation kinetics, and the charge-recombination kinetics. To this end, the binding constants, which ranged from log K=3.94-4.38, are dominated by axial coordination, with minor contributions from the orbital overlap of the curved and planar π systems. The charge-separation and charge-recombination kinetics, which are in the order of 10 and 10 s, relate to the reduction potential of the fullerene and metallofullerenes, respectively. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Endohedral metallofullerenes-filled fullerene derivatives towards multifunctional reaction center mimics - Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Feng, Lai; Tsuchiya, Takahiro; Akasaka, Takeshi; Echegoyen, Luis (Chemistry - A European Journal, 2012)
In recent years, endohedral metallofullerenes have attracted tremendous interest not only in physics and chemistry, but also in interdisciplinary areas, such as materials and biological sciences. In this concept article we highlight recent results on different endohedral metallofullerenes based on lanthanides and their derivatives. The chemical and excited state reactivities of endohedral metallofullerenes are discussed for various endohedral clusters. Most important is the part that covers spectroscopic and kinetic assays of reductive and oxidative charge transfer evolving from photoexcited electron donors and electron acceptors, respectively, in a variety of electron donor-acceptor conjugates. Towards this end, we refer to the applications of endohedral metallofullerenes in photovoltaic devices that feature greater efficiency than devices fabricated with empty fullerenes. Herein, we focus mainly on results obtained in the groups of Akasaka, Echegoyen, and Guldi. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Geometric influence on intramolecular photoinduced electron transfer in platinum(II) acetylide-linked donor-acceptor assemblies - Molina-Ontoria, Agustin; Rivera-Nazario, Danisha M.; Tigreros, Alexis; Ortiz, Alejandro; Nunez, Jose E.; Insuasty, Braulio; Lüders, Daniela; Wolfrum, Silke; Guldi, Dirk Michael; Echegoyen, Luis (Chemistry - A European Journal, 2014)
A new donor-acceptor system, in which the electron donor triphenylamine (TPA) and the electron acceptor C60 are bridged through a cis- or trans-platinum(II) acetylide spacer have been prepared. Ground-state studies were conducted using electrochemistry and UV/Vis spectroscopy. Fluorescence studies suggested that charge transfer is the deactivation mechanism for the singlet excited state, and this was verified by transient absorption spectroscopy. Selective photoexcitation of 1 and 2 at 387 nm leads to a fast charge transfer between the TPA and C60, which gives rise to a radical ion-pair state (TPA.+-Pt-C60.-). Our results suggest that charge transfer is favored for the cis configuration while the presence of the trans configuration in the PtII diacetylide results in a longer-lived charge separated states. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electron transfer; excited states; fullerenes; platinum(II) acetylide; triphenylamine

Scrutinizing the chemical nature and photophysics of an expanded hemiporphyrazine: The special case of [30]trithia-2,3,5,10,12,13,15,20,22,23,25, 30-dodecaazahexaphyrin - Trukhina, Olga N.; Rodriguez-Morgade, M. Salome; Wolfrum, Silke; Caballero, Esmeralda; Snejko, Natalia; Danilova, Elena A.; Gutierrez-Puebla, Enrique; Islyaikin, Mikhail K.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
Thirty π-electron-expanded hemiporphyrazines 1a-c have been prepared by crossover condensation reaction of 2,5-diamino-1,3,4-thiadiazole and the corresponding phthalonitrile (3) or diiminoisoindoline (4) derivatives. The expanded azaporphyrin hexamers have been unequivocally characterized by means of spectroscopic, crystallographic, and electrochemical techniques. Weak intramolecular hydrogen bonding imposes a planar conformation to macrocycles. However, the overall electronic delocalization is low, and the nature of the resulting [30]heteroannulene is nonaromatic, as confirmed by NMR studies, XR diffraction analysis, and calculation of the NICS(0) value. Studies on a wide range of physicochemical features including ground, excited, reduced, and oxidized states provide evidence for the wide applicability of these 30 π-electron-expanded hemiporphyrazines in processes involving electron transfer. A key asset of our work is the systematic development of spectroscopic and kinetic markers for the formation and decay of all of the aforementioned species. Thirty π-electron-expanded hemiporphyrazines evolve as broadly absorbing light harvesters with excited state energies of around 2.3 eV that are susceptible to facile one-electron reduction and one-electron oxidation reactions. © 2010 American Chemical Society.

Stabilizing ion and radical ion pair states in a paramagnetic endohedral metallofullerene/π-extended tetrathiafulvalene conjugate - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
Electron donor-acceptor conjugates of paramagnetic endohedral metallofullerenes and π-extended tetrathiafulvalene (exTTF) were synthesized, characterized, and probed with respect to intramolecular electron transfer involving paramagnetic fullerenes. UV-vis-NIR absorption spectroscopy complemented by electrochemical measurements attested to weak electronic interactions between the electron donor, exTTF, and the electron acceptor, La@C , in the ground state. In the excited state, photoexcitation powers a fast intramolecular electron transfer to yield an ion and radical ion pair state consisting of one-electron-reduced La@C and of one-electron-oxidized exTTF. © 2012 American Chemical Society.

Topological and conformational effects on electron transfer dynamics in porphyrin-[60]fullerene interlocked systems - Megiatto, Jackson D.; Schuster, David I.; De Miguel Rojas, Gustavo; Wolfrum, Silke; Guldi, Dirk Michael (Chemistry of Materials, 2012)
The effect of molecular topology and conformation on the dynamics of photoinduced electron transfer (ET) processes has been studied in interlocked electron donor-acceptor systems, specifically rotaxanes with zinc(II)-tetraphenylporphyrin (ZnP) as the electron donor and [60]fullerene (C ) as the electron acceptor. Formation or cleavage of coordinative bonds was used to induce major topological and conformational changes in the interlocked architecture. In the first approach, the tweezer-like structure created by the two ZnP stopper groups on the thread was used as a recognition site for complexation of 1,4-diazabicyclo[2.2.2]octane (DABCO), which creates a bridge between the two ZnP moieties of the rotaxane, generating a catenane structure. The photoinduced processes in the DABCO-complexed (ZnP) -[2]catenate-C system were compared with those of the (ZnP) -rotaxane-C precursor and the previously reported ZnP-[2]catenate-C . Steady-state emission and transient absorption studies showed that a similar multistep ET pathway emerged for rotaxanes and catenanes upon photoexcitation at various wavelengths, ultimately resulting in a long-lived ZnP /C charge-separated radical pair (CSRP) state. However, the decay kinetics of the CSRP states clearly reflect the topological differences between the rotaxane, the catenate, and DABCO-complexed-catenate architectures. The lifetime of the long-distance ZnP -[Cu(I)phen ] -C CSRP state is more than four times longer in 3 (1.03 μs) than in 1 (0.24 μs) and approaches that in catenate 2 (1.1 μs). The results clearly showed that creation of a catenane from a rotaxane topology inhibits the charge recombination process. In a second approach, when the Cu(I) ion used as the template to assemble the (ZnP) -[Cu(I) phen ] -C rotaxane was removed, it was evident that a major structural change had occurred. since charge separation between the chromophores was no longer observed upon photoexcitation in nonpolar as well as in polar solvents. Only ZnP and C triplet excited states were observed upon laser excitation of the Cu-free rotaxane. These results highlight the critical importance of the central Cu(I) ion for long-range ET processes in these nanoscale interlocked electron donor-acceptor systems. © 2012 American Chemical Society.

Utilization of Sc3N@C80 in long-range charge transfer reactions - Wolfrum, Silke; Pinzon, Julio R.; Molina-Ontoria, Agustin; Gouloumis, Andreas; Martin, Nazario; Echegoyen, Luis; Guldi, Dirk Michael (Chemical Communications, 2011)
Electron accepting Sc N@C promotes long-range charge transfer events evolving from photoexcited metalloporphyrins to afford radical ion pair states with lifetimes in the range of μs. © 2011 The Royal Society of Chemistry.